ADO09, a co‐formulation of the amylin analogue pramlintide and the insulin analogue A21G, lowers postprandial blood glucose versus insulin lispro in type 1 diabetes. Issue 4 (18th January 2021) - Andersen, Grit; Meiffren, Grégory; Famulla, Susanne; Heise, Tim; Ranson, Aymeric; Seroussi, Cyril; Eloy, Rosy; Gaudier, Martin; Charvet, Richard; Chan, You‐Ping; Soula, Olivier; DeVries, J. Hans
Abstract: Aim: To compare the safety, pharmacokinetics and pharmacodynamics of ADO09 with insulin lispro (Lispro) and separate subcutaneous injections of human insulin and pramlintide (Ins&Pram) in 24 subjects with type 1 diabetes. Methods: At three dosing visits, participants received single doses of ADO09, Ins&Pram or Lispro immediately before eating a standardized mixed meal together with 1 g of acetaminophen, which was used as a surrogate marker to evaluate the kinetics of gastric emptying. Premeal blood glucose was adjusted to 126 mg/dL ± 10% by means of insulin and glucose infusions. The insulin dose was 7.5 U and the pramlintide dose was 45 μg. Blood glucose, glucagon and acetaminophen concentrations were assessed as pharmacodynamic endpoints; insulin and pramlintide concentrations were analysed as pharmacokinetic endpoints, and safety and tolerability were assessed. Results: Compared with Lispro, ADO09 reduced postprandial blood glucose (ppBG) excursions by more than 95% in the first hour postmeal (mean ± SD ∆AUC BG 0‐1 h: 1.4 ± 9.9 mg*h/dL vs. 43.5 ± 15.3 mg*h/dL; p < .0001). Maximum ppBG was significantly improved with ADO09 (∆BGmax 87.0 ± 35.5 mg/dL) versus both Lispro (109.2 ± 31.1 mg/dL; p = .0133) and Ins&Pram (109.4 ± 44.3 mg/dL; p = .0357). Gastric emptying with ADO09 was similar to Ins&Pram and significantly slower than with Lispro. All treatments were well tolerated and both adverse events and hypoglycaemic events were rare during the meal test procedure. Conclusion: ADO09 was well tolerated and markedly reduced ppBG compared with Lispro. ADO09 formulation was generally similar to the separate administration of insulin and pramlintide, except for a better BG level in the 4‐8 h interval postmeal. These positive results warrant further investigations with ADO09.